Habitat use by two tropical species of waterfowl in central Malaysia - Salari, Abdollah; Zakaria, Mohamed; Boyce, Mark S. (Wildfowl, 2016)
Two tropical species of waterfowl, the Lesser Whistling-duck (LWD) Dendrocygna javanica and Cotton Pygmy-goose (CPG) Nettapus coromandelianus, are patchily distributed across Malaysia and little is known about their habitat requirements. We studied patterns of habitat use for LWD and CPG at the Paya Indah Wetlands Reserve, Malaysia (c. 3,050 ha), by counting the birds from observation points and using a zero-altered negative binomial model to describe their abundance and distribution at the site. Habitat use by LWD and CPG was highly correlated; for instance both species frequented shallow, nutrient-rich lakes in the study area. Fine-scale measures of vegetation characteristics influenced local distribution, whereas a combination of anthropogenic activities and other habitat features best predicted abundance. Overall, LWD selected the more stable but densely-vegetated marshy shoreline while CPG used vegetated areas near the central deeper portions of the lake. Our habitat-selection models give insight into the ecology of LWD and CPG in Malaysia and can provide a tool for identifying areas for possible habitat restoration and conservation in the region.